User preference-aware navigation for mobile robot in domestic via defined virtual area. (1st January 2021) - Zhang, Ying; Zhang, Cui-Hua; Shao, Xuyang
Abstract: Human-aware robot navigation is the key to facilitate the deployment of mobile robots into human–robot shared environments. Although many efforts have been made in this regard, almost all of the existing works focus on the constraints such as user comfort and social rules, while ignoring to consider user preferences. And it is expected that the mobile robot is able to navigate in the user-desired areas according to user preferences, e.g., navigating at low speed in the bedroom. To this end, this paper studies the problem of allowing users to control the robot's working areas to ensure robot aware navigation based on their preferences. To address the intrusiveness of additional facilities or devices to users, we propose a non-intrusive solution by deploying the virtual areas that are non-physical areas but are respected by the mobile robot while performing navigation tasks. Farther, an interactive interface is developed to support the common (non-expert) users to flexibly define the desired areas and specify the navigation behavior of the robot according to their preferences. The proposed solution is fully evaluated through extensive experiments. Experimental results are presented to demonstrate the validity of our approach, and show that the mobile robot can change its navigation behavior in user-defined areas according to user preferences. Supplementary video can be available at https://youtu.be/oXtbNavLmMk .